Mucocele of the dorsal surface of the tongue: A case report - Titsinides, Savvas (J Clin Exp Dent, 2018)
Mucoceles represent one of the most common lesions of the oral cavity, developing as a result of saliva accumulation. The most frequent affected area is the lower lip, followed by floor of mouth, ventral tongue and buccal mucosa. Despite numerous reports of mucoceles originating on the ventral surface of the tongue, only scarce cases of such a lesion identified on the dorsal tongue surface have been described. In this report a mucocele developed on the dorsal tongue of a 74-year-old woman is described. Additionally a review of previously published mucoceles of the dorsal surface of the tongue is provided and discussed. A 74-year-old female patient was referred for a painless swelling on the dorsal surface of the tongue of 1 month duration. Possible clinical diagnosis included granular cell tumor and lingual thyroid gland. Proper blood testing for TSH, T3 and T4 as well as ultrasonography were requested, found to be within normal limits. An excisional biopsy was performed and tumor was removed with no intra-operative complications. Histopathological examination was consistent with a mucocele, exhibiting an amorphous material surrounded by granular connective tissue without epithelial lining on the periphery. Patient was examined on regular follow-up basis, with no signs of recurrence for the last 1 year. Mucoceles of the dorsal tongue surface represent rare clinical entities, necessitating the need for further case reports to be published in order to widen our understanding of their clinical features. Key words:Mucocele, oral cavity, tongue, minor salivary glands, oral and maxilloafcial pathology.